Influence of menopause and obstetric-gynaecological history on the quality of life in 45-65-year old women - Żołnierczuk-Kieliszek, Dorota; Kulik, Teresa Bernadetta; Wiktor, Henryk; Pacian, Anna; Stefanowicz, Agata (Polish Journal of Public Health, 2010)
Aim. The aim of the research was to determine if the qua-lity of life of women depends on their menopausal status and their obstetrical and gynecological past. Material and methods. The study was carried out with the survey method, with the postal questionnaire technique. Three standardized questionnaires: WHOQOL-BREF, Women’s Health Questionnaire (WHQ) and SF-36 were used as research tools. An author-designed questionnaire was also used. The questionnaires were sent to a representative sample of 7,875 women between 45 and 65 years old, living in the Lublin province, in 2007. The mail addresses were obtained from the Local Data Bank of the Lublin Provincial Office. We received 2,143 replies (feedback 27.2%). The statistical analysis of the obtained data was performed. The domains of quality of life defined by the WHOQOL, WHQ, SF-36 questionnaires were treated as dependent variables, the data from women’s obstetrical and gynaecolo-gical past were treated as independent variables. Results. Postmenopausal women (natural or surgical menopause) revealed a significantly worse quality of life than pre- and perimenopausal women. The women who had an abortion and the respondents who currently suffered from gynaecological diseases demonstrated a significantly worse quality of life. Women suffering from urinary incontinence showed a significantly worse quality of life than the respondents free from this complaint. The logistic regression analysis proved that urinary incontinence was among the strongest predictors of a decreased quality of life. No statistical relationship was found between the women’s age of menarche and the number of pregnancies and labours, and the women’s quality of life.